Mesoporous nanosilica-supported polyoxomolybdate as catalysts for sustainable desulfurization - Mirante, Fátima (2019)
Mesoporous silica nanoparticles (MSNs) strategically functionalized were used to immobilize a homogeneous polyoxomolybdate catalyst [PMo12O40]3- (PMo12), active but unstable. The PMo12@TBA-MSN composite (where TBA refers to surface-tethered tributylammonium groups) conferred high stability to the polyoxomolybdate catalytic center and displayed an increase in efficiency for the oxidative desulfurization (ECODS) of a diesel simulant under sustainable conditions (using H2O2 as oxidant and an ionic liquid, [BMIM]PF6, as solvent). Continuous reuse of the catalyst and ionic liquid solvent in consecutive ECODS cycles was successfully performed, avoiding the production of residual wastes. The performance of the PMo12@TBA-MSN catalyst improved upon its reuse, leading to complete desulfurization of a multicomponent model diesel containing benzothiophene derivatives after just 1 h of the catalytic stage of the process. The robust nature of the supported catalyst was indicated by characterization of the recovered solid which showed retention of the structural and chemical integrities.